Grön asfalt och NCC - Svensson, Simon (2005)
NCC ROADS Sweden east is a part of the NCC Corporation. The company mainly produces aggregates, asphalt and concrete. They have taken the environmental issues seriously and been working with that since the middle of the nineties. When manufacturing asphalt large a quantity of fossil energy is needed. The company is now about to make further progresses by manufacturing environmental friendly asphalt ("green asphalt") with using bio-energy. With the concept "green asphalt" means asphalt produced with using bio-energy instead of fossil energy when heating the asphalt mix. This study tries to find out if there is any market for environmental friendly manufactured asphalt. The purpose of this study has also been to find out if there is any market-benefits in offering "green asphalt" on the market. And if its possible to get more profit out of it. The market research has been confined to the public sector. Swedish road administration and communities consume the main part of the asphalt in Sweden. As a conclusion it can be said that some extra profit can be made by selling "green asphalt". But the main part of the costs of investing in "green asphalt" has to be charged on the good-will account, at least at the first years. By increased market shares and increased selling the investments can be paid back on a long view. Producing environmental friendly asphalt in a sustainable way is probably a big step to take.